Pengaruh Stres Kerja Dan Lingkungan Kerja Terhadap Turnover Intention Karyawan PT. Sentra Duta Sakti Jakarta Utara - Aldino, Aldino; Krishantoro, Krishantoro; Aziz, Abdul (JAMBIS : Jurnal Administrasi Bisnis, 2024)
High turnover intention can give a negative impact on organizational effectiveness because companies lose experienced human resources and have to invest time and efforts to train new employees. This study is intended to find out the effects of work stress and work environment on the turnover intention of employees of PT. Sentra Duta Sakti North Jakarta. This study uses a quantitative method. Data collection techniques are in the form of questionnaires and literature. Population in this study are employees of PT. Sentra Duta Sakti North Jakarta. Sampling techniques in this study are saturated samples (total sampling) with total samples of 110. The results of this study indicate that work stress and work environment give positive and significant effects on employee turnover intention of 76.9%.